Susceptibility of different hepatitis B virus isolates to interferon-alpha in a mouse model based on hydrodynamic injection. - Jingjiao Song; Yun Zhou; Sheng Li; Baoju Wang; Xin Zheng; Jun Wu; Kathrin Gibbert; Ulf Dittmer; Mengji Lu; Dongliang Yang (PLoS ONE, 2014)
Interferon alpha (IFN-α) is commonly used for the treatment of chronic hepatitis B (CHB) patients. Many factors including viral genetics may determine the outcome of IFN-α therapy. In this study, we tested whether the expression of IFN-α directly in the liver inhibits HBV gene expression and replication using a HBV hydrodynamic injection (HI) mouse model. Two replication-competent clones from different HBV isolates that belonging to HBV genotype A and B based on a pAAV vector (pAAV-HBV-A and pAAV-HBV-B) were compared for their susceptibility to IFN-α. HBV clones were injected into mice either alone or in combination with a murine (m) IFN-α expression plasmid (pmIFN-α). HBsAg and HBeAg concentrations and HBV DNA levels in mice differed after injection of these two HBV clones. Co-application of pmIFN-α together with the two distinct isolates resulted in markedly different kinetics of decline of HBsAg, HBeAg, and HBV DNA levels in the mice. Immunohistochemical staining of liver sections with anti-HBc showed that mIFN-α application completely inhibited the expression of HBcAg in mice inoculated with pAAV-HBV-B, whereas the expression of HBcAg was only reduced in mice with pAAV-HBV-A. Consistently, mice injected with pAAV-HBV-B and pmIFN-α showed higher expression levels of the IFN-stimulated genes (ISGs) ISG15, OAS, PKR as well as proinflammatory cytokine IL-6 in the liver. In addition, expression levels of anti-inflammatory cytokine IL-10 was down-regulated significantly in liver of the mice injected with pAAV-HBV-B and pmIFN-α. Our data demonstrate that IFN-α exerts antiviral activity in HBV mouse model, but different HBV isolates may have diverse susceptibility to IFN-α.